Eficiência energética em ambientes de ensino - Copetti, Guilherme Luiz Zancan (Universidade Federal do Pampa, 2013)
The aim of this study is to analyze the current lighting systems of classrooms and libraries of campis of Bagé-RS, Dom Pedrito and Jaguarão-RS belonging to the Federal University of Pampa. The main motivation for this study was the fact that there is a concern in relation to conditions of illuminance for those teaching environments. Through visits to the campus were detected some inadequacies relating to bright comfort after this observation, it became necessary to carry out further investigation, which will be detailed in this work. The present work aims to propose alternatives to the improvement of luminous comfort in libraries and class-rooms of the Federal University of Pampa. Manager studies were carried out in all educational environments, using software DIALUX to analyze in depth the lighting system. Starting from the current scenario, which basically uses a lighting system with overlapped lamps 4x32W milky background, these allocated with a certain orientation, it was proposed to create various lighting scenarios, with different allocations to the fixtures and use of a more efficient system to guarantee the same levels of illuminance, seeking the reduction of energy consumption, taking into account the contribution of natural lighting. For this analysis, we used the DIALUX software for realization of modeling of class-rooms and libraries in study. It was possible to measure the average illuminance levels to make a horizontal and vertical comparisons of current scenarios with those proposed, aiming the light and comfort the reduction of energy consumed. The idea is to provide suitable conditions of comfort and efficiency of lighting system for students and teachers in classrooms and libraries. Analyzing the current situation layouts of buildings, classrooms and libraries and proposing changes in today's lighting systems, seeking to ensure the comfort lumínico for people using the environments in question, by maintaining appropriate lighting levels. Pro-pose the creation of more efficient lighting systems, seeking to reduce energy costs.
Keywords: Electrical engineering; Lighting; Energy efficiency; Electric power consumption; CNPQ::ENGENHARIAS; Engenharia elétrica; Iluminação; Eficiência energética; Consumo de energia elétrica